Airborne PAHs and PCBs along a coastal, urban-industrial gradient in Rio de la Plata Estuary, Argentina - Astoviza, Malena Julia (2017)
Atmospheric transport is the principal route of transference of Semivolatile Organic Compounds (SVOCs) from local to global distances. Airborne SVOCs such as Polycyclic aromatic hydrocarbons (PAHs) and Polychlorinated Biphenyls (PCBs) are included in the POP protocol under the Convention on Long-Range Transboundary Air Pollution (LRTAP) and the Stockholm Convention due to their toxicity and environmental persistence. Owing to their practicality (autonomous, easy handled and affordable), in the last decades, polyurethane foam passive air samplers (PUF-PAS) have been widely used to evaluate spatial and temporal patterns of SVOCs allowing a higher temporal resolution than active air samplers. La Plata city, capital of Buenos Aires state, is located 15 km away from the Rio de la Plata Estuary coast, in a highly industrialized (major oil refinery of the country and associated industries [4], an important shipyard and container port) and densely populated region of the country (about 1,000,000 inhabitants). In this study, we report the patterns of airborne PAHs and PCBs along a transitional gradient from the coast to urban-suburban area of La Plata City in order to evaluate their sources, composition and spatial variability.